Improvement Proposals for the Machining Production Process in the Environmentally Responsible Manufacturing Perspective - Karakuş, Güzide; Karakuş, Feridun; Koçak, Ozan (European Journal of Sustainable Development, 2021)
In today's world, where we are experiencing the fourth industrial revolution, technological change and transformation cause significant changes in human life. Information, technology, and industrialization are the most critical issues for a sustainable life and are also crucial for an efficient supply chain. However, global environmental problems and new epidemic diseases cause significant damage to life quality. Although the individual impact on environmental pollution is known, it cannot be compared with industrial impact. Commercial activities cause high levels of environmental damage. Unfortunately, the environmental aspect of sustainability does not receive the necessary attention, and practices do not go beyond legal frameworks. Businesses are reluctant to engage in environmentally friendly activities due to the belief that they will not increase profitability. However, the destruction caused by industrialization to the environment can no longer be left to the initiative of the companies. Businesses should evaluate their manufacturing processes by considering environmental impacts and reorganize within the framework of cleaner production methodology. This study aims to develop suggestions for improving the machining production process, one of the most used manufacturing methods worldwide, from an environmentally friendly perspective. The authors' expertise was used in the study with the experimental research technique based on observation, expert interviews, and document review. In consequence of the study, suggestions for reducing emissions, swarf waste, wastewater, waste oil, and energy consumption to minimize the environmental damage of the machining production process were presented.